Protective Effect of Lemongrass Extract (Cymbopogon nardus) on Spermatozoa Cells Induced by Lead Acetate - Putri Ayu Ika Setiyowati; Rofiatun Solekha; Dwi Dianita Irawan; Reny Rosalina; Karin Alifia Rachmadani; Angella Ananda Saputra (Biomolecular and Health Science Journal, 2022)
Introduction: Male infertility can be caused by many factors. One of which is environmental pollution such as lead acetate. Lead acetate exposure can increase Reactive Oxygen Species (ROS), affecting spermatozoa quality. Natural antioxidants and flavonoid on Lemongrass (C. nardus) have a great potential for protecting the male reproductive system. This study aimed to analyze the effect of giving various dosages of C. nardus extract on the sperm quality of mice. Methods: The Balb/C male mice were divided into five equal groups. The negative control group was injected with 0.01 ml Na-CMC 0.5% within 40 days, and the positive control group was injected with 0.01 ml lead acetate 7 mg/kg BW within 5 days, the treatment groups were injected by 0.01 ml lead acetate 7 mg/kg body weight within 5 days and continuously injected by 0.01 ml of C. nardus extract with various dosage 25 mg/kg BW, 50 mg/kg BW, and 100 mg/kg BW within 35 days. At the end of the experiment, mice were sacrificed, and sperm suspensions were collected from cauda epididymal to measure the morphology, concentration, and motility.Results: The results showed that giving C. nardus extract could repair morphology, concentration, and motility of spermatozoa with significantly different (p<0.05). The 25 mg/kg BW dose has a good protective effect. Conclusion: The C. nardus extract can repair the decreasing sperm quality caused by lead acetate exposure.